Millennium generation financial literacy and fintech awareness - Jeevitha, R; Amaleshwari, U. (BOHR International Journal of Finance and Market Research, 2023)
The growth of rapid financial technology (fintech) is expected to contribute more than 12% of compound annual growth rate (CAGR) to the economy. India is gradually becoming the hub for many prominent fintech startups such as Paytm, Pine Labs, PayU, Razorpay, and others. However, as per the survey by Financial Express, only 27% of Indians are financially literate. This article investigates the factors that influence the millennial generation and their financial literacy and the relationship between their knowledge, their objectives, their outlook, and their behavior toward the use of fintech applications. The questionnaire is used to gather the main data. Chi squared analysis was used to test the hypotheses, and correspondence analysis was used to determine the characteristics of the millennial generation and visually demonstrate the discrepancy.